Peningkatan Hasil Belajar PAI Melalui Model Problem Based Learning di Kelas VII UPTD SMPN 2 Kecamatan Suliki - Yeni Warni; Salmiwati Salmiwati; Rina Mala Putri (Jurnal Pendidikan Tuntas, 2024)
Education aims to improve the quality and quantity of students. The selection of the right learning model in the learning process greatly affects the high and low learning outcomes of students. The learning model is an approach that can be taken by educators so that the teaching and learning process runs effectively so that educational goals are achieved. The problem in this study is the low learning outcomes of students in Islamic Religious Education subjects because the learning model used is still not varied and conventional. To overcome these problems, researchers applied the Problem Based Learning (PBL) Model with the aim of improving Islamic Education learning outcomes in class VII UPTD SMPN 2 Suliki District. This research uses the type of classroom action research (PTK). The subjects in this study were students of class VII UPTD SMPN 2 Suliki District, totaling 10 students consisting of 6 male students and 4 female students. Classroom action research was carried out in two cycles, each cycle consisting of one meeting. In this study there are four stages, namely planning, implementation, observation and reflection. Data collection was carried out using observation and written tests. Based on the results of the study, it shows that the average learning outcomes of students have increased. It is known that the KKTP value that has been determined from the school is 70. In pre-research, it is known that 4 students have reached KKTP with a percentage of 40% and 6 students have not reached KKTP with a percentage of 60%. In cycle I, it has increased as many as 6 students have reached KKTP with a percentage of 60% and 4 students have not reached KKTP with a percentage of 40%. Furthermore, in cycle II there has been an increase of 10 students with a percentage of 100%.